2004
DOI: 10.1152/physiolgenomics.00040.2004
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of gene expression after transverse aortic constriction in mice

Abstract: Zhao, Mingming, Amy Chow, Jennifer Powers, Giovanni Fajardo, and Daniel Bernstein. Microarray analysis of gene expression after transverse aortic constriction in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 51 publications
(34 reference statements)
8
67
1
Order By: Relevance
“…We assessed the effects of TAC on heart weight/body weight ratios and gene expression after only 7 days, and as such we addressed mechanisms related to the compensatory (growth) phase of hypertrophy unrelated to a transition to heart failure. Using a similar murine pressure overload model, Zhao and coworkers [29] reported most genes were differentially regulated by 10 days, similar to the time period used in this study. Wagner and coworkers have shown that TAC resulted in stabilization of hypertrophy in as few as 20 days in mice [30].…”
Section: Discussionsupporting
confidence: 64%
“…We assessed the effects of TAC on heart weight/body weight ratios and gene expression after only 7 days, and as such we addressed mechanisms related to the compensatory (growth) phase of hypertrophy unrelated to a transition to heart failure. Using a similar murine pressure overload model, Zhao and coworkers [29] reported most genes were differentially regulated by 10 days, similar to the time period used in this study. Wagner and coworkers have shown that TAC resulted in stabilization of hypertrophy in as few as 20 days in mice [30].…”
Section: Discussionsupporting
confidence: 64%
“…During the early "asymptomatic" stage of diastolic dysfunction (1 month), there were surprisingly minimal gene expression changes, a marked contrast to previous studies of isolated PS, isolated PI, or models of LV afterload, such as transverse aortic constriction (TAC) (17)(18)(19). Only 23 genes were upregulated, including those encoding proteins involved in metabolic (insulin-like receptors, adenylate cyclase), transport (organic anion transporters), and fibrotic (fibroblast growth factors) pathways, while 33 were downregulated, including those encoding proteins involved with pathways related to oxidative stress (NADPH oxidase 4, glutathione transferase) and chemokine response (chemokine ligands, adhesion molecules).…”
Section: Model Of Pi+ps Recapitulates the Clinical Setting -Early Diacontrasting
confidence: 72%
“…TAC was performed as previously described (53). Briefly, anesthesia was induced with 3% isoflurane and maintained with 1.5% isoflurane.…”
Section: Methodsmentioning
confidence: 99%
“…We subjected ␤ 1 , ␤ 2 , and ␤ 1 ␤ 2 -AR knockout mice to transverse aortic constriction (TAC) at a level that induces stable, compensated LV hypertrophy and not cardiac failure (53). These conditions were chosen to specifically study the separate mechanisms of hypertrophy as distinct from hypertrophy-induced heart failure.…”
mentioning
confidence: 99%